Observation of K-Shell Soft X Ray Emission of Nitrogen Irradiated by XUV-Free Electron Laser FLASH at Intensities Greater than 10(16) W/cm(2) - Galtier, E; Rosmej, F; Renner, O; Juha, L; Chalupsky, J; Gauthier, J; White, S; Riley, D; Vinko, S; Witcher, T; Wark, J; Nagler, B; et al. (2011)
In the past few years, the development of light sources of the 4th generation, namely XUV/X-ray Free Electron Lasers provides to the scientific community outstanding tools to investigate matter under extreme conditions never obtained in laboratories so far. As theory is at its infancy, the analysis of matter via the self-emission of the target is of central importance. The characterization of such dense matter is possible if photons can escape the medium. As the absorption of K-shell X-ray transitions is minimal, it plays a key role in this study. We report here the first successful observation of K-shell emission of Nitrogen at 430 eV using an XUV-Free Electron Laser to irradiate solid Boron Nitride targets under exceptional conditions: photon energy of 92 eV, pulse duration of ∼20 fs, micro focusing leading to intensities larger than 1016 W/cm2. Using a Bragg crystal of THM coupled to a CCD, we resolved K-shell line emission from different charge states. We demonstrate that the spectroscopic data allow characterization of electron heating processes when X-ray radiation is interacting with solid matter. As energy transport is non-trivial because the light source is monochromatic, these results have an important impact on the theory. © 2011 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.